Numerical investigation of monodisperse granular flow through an inclined rotating chute. Issue 10 (30th June 2014) - Shirsath, Sushil S.; Padding, Johan T.; Kuipers, J. A. M. (Hans); Peeters, Tim W. J.; Clercx, Herman J. H.
<x xml:space="preserve">Abstract</x> A discrete element model of spherical glass particles flowing down a rotating chute is validated against high quality experimental data. The simulations are performed in a corotating frame of reference, taking into account Coriolis and centrifugal forces. In view of future extensions aimed at segregation studies of polydisperse granular flows, several validation steps are required. In particular, the influence of the interstitial gas, a sensitivity study of the collision parameters, and the effect of system rotation on particle flow is investigated. Shirsath et al. have provided the benchmark laboratory measurements of bed height and surface velocities of monodisperse granular flow down an inclined rotating chute. With a proper choice of the friction coefficients, the simulations show very good agreement with our experimental results. The effect of interstitial gas on the flow behavior is found to be relatively small for 3‐mm granular particles. © 2014 American Institute of Chemical Engineers AIChE J, 60: 3424–3441, 2014